2000
DOI: 10.1002/chin.200036013
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Coalescence of Single‐Walled Carbon Nanotubes.

Abstract: structure structure (solids and liquids) D 2000 -013Coalescence of Single-Walled Carbon Nanotubes. -The coalescence of single-walled carbon nanotubes, produced with Ni-Y catalysts in a C arc is investigated by in situ electron irradiation and heating (800 • C) in a high resolution transmission electron microscope. Tight-binding molecular dynamics and Monte Carlo calculations are performed. Among other defects, vacancies produced by electron irradiation are most important in directing the coalescence of nanotub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 1 publication
0
26
0
Order By: Relevance
“…215,216 Another widely used parametrization for carbon by Xu et al 217 has been successfully applied to simulations of irradiation effects in carbon nanomaterials. 12,18,218 …”
Section: E Tight-binding Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…215,216 Another widely used parametrization for carbon by Xu et al 217 has been successfully applied to simulations of irradiation effects in carbon nanomaterials. 12,18,218 …”
Section: E Tight-binding Methodsmentioning
confidence: 99%
“…Experiments carried out for the technologically important carbon nanomaterials, such as nanotubes and graphene, showed that their atomic structure and morphology can be changed in a controllable manner by irradiation. [6][7][8][9][10][11][12][13][14][15][16] Besides, it was demonstrated that nanotubes can be interconnected or merged 9,12,17,18 and that irradiation can give rise to many interesting phenomena, such as extreme pressure inside nanotubes 19 or fullerenelike "onions," 6,20 so that these systems can be used as nanolaboratories for studying pressure-induced transformations at the nanoscale. Furthermore, recent experiments indicate that ion, [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] electron, 6,39-52 and high energy photon [53][54][55][56] irradiation can be used to tailor the mechanical, 8,10 electronic, 11,…”
Section: Introductionmentioning
confidence: 99%
“…The common structural defects existing in CNTs are atomic vacancies and topologic defects, of which the former corresponds to the deficiency of carbon atoms in a CNT, and the latter is associated with the network topology deviated from the hexagon rings. These defects have been studied extensively both theoretically and experimentally [15][16][17][18][19][20][21][22][23][24][25][26][27]. Experiments observe that carbon nanotubes can be released under electrons or ions irradiation [16,22], leaving behind vacancies in CNTs.…”
Section: Introductionmentioning
confidence: 97%
“…Band gap tailoring and carbon nanotube interconnects have been achieved using charged particle beams as well. [4][5][6][7] Furthermore, it appears that it is possible to modify their physical properties by changing their structure locally only along a short section of the tube. 8 Most of the works devoted to study the effects of electron or ion-beam irradiation have involved single-walled and multiwalled carbon nanotubes.…”
Section: Introductionmentioning
confidence: 99%